Green care in first-episode psychosis: short report of a mixed-methods evaluation of a 'woodland group' in an early intervention service. (August 2021) - Cuthbert, Sharon; Sharp, Harriet; Berry, Clio
Abstract : Aims and method: In the context of increasing recognition of the role of nature in well-being, but limited evidence for specific patient groups, we describe a mixed-methods evaluation of a 10-week green care intervention (a woodland group) for 18- to 30-year-olds who had experienced a first episode of psychosis. Data were collected using the Questionnaire on the Process of Recovery (QPR), semi-structured service evaluation questionnaires, the NHS Friends and Family Test (FFT), and focus group analysis. Results: All participants present at week 10 ( n = 5) would recommend this group to others; 4/8 participants showed reliable improvement on QPR outcome measures. Thematic analysis identified themes of connection with nature and others, development of a sense of well-being and 'peacefulness' and new perspectives on psychotic experience. Clinical implications: This small retrospective evaluation describes patient-reported benefits, feasibility and acceptability of green care interventions within early intervention in psychosis services (EIS).